The potential of genome-wide RAD sequences for resolving rapid radiations: a case study in Cactaceae - Bombonato, Juliana Rodrigues; do Amaral, Danilo Trabuco; Silva, Gislaine Angélica Rodrigues; Khan, Gulzar; Moraes, Evandro M.; da Silva Andrade, Sónia Cristina; Eaton, Deren A.R.; Alonso, Diego Peres [UNESP]; Ribolla, Paulo Eduardo Martins [UNESP]; Taylor, Nigel; Zappi, Daniela; Franco, Fernando Faria (Elsevier, 2020)
The reconstruction of relationships within recently radiated groups is challenging even when massive amounts of sequencing data are available. The use of restriction site-associated DNA sequencing (RAD-Seq) to this end is promising. Here, we assessed the performance of RAD-Seq to infer the species-level phylogeny of the rapidly radiating genus Cereus (Cactaceae). To examine how the amount of genomic data affects resolution in this group, we used datasets and implemented different analyses. We sampled 52 individuals of Cereus, representing 18 of the 25 species currently recognized, plus members of the closely allied genera Cipocereus and Praecereus, and other 11 Cactaceae genera as outgroups. Three scenarios of permissiveness to missing data were carried out in iPyRAD, assembling datasets with 30% (333 loci), 45% (1440 loci), and 70% (6141 loci) of missing data. For each dataset, Maximum Likelihood (ML) trees were generated using two supermatrices, i.e., only SNPs and SNPs plus invariant sites. Accuracy and resolution were improved when the dataset with the highest number of loci was used (6141 loci), despite the high percentage of missing data included (70%). Coalescent trees estimated using SVDQuartets and ASTRAL are similar to those obtained by the ML reconstructions. Overall, we reconstruct a well-supported phylogeny of Cereus, which is resolved as monophyletic and composed of four main clades with high support in their internal relationships. Our findings also provide insights into the impact of missing data for phylogeny reconstruction using RAD loci.
Keywords: Cereus; ddRAD-Seq; Missing data; Phylogenomics; Radiation